A comparative study of flexural and shear behavior of ultra-high-performance fiber-reinforced concrete beams. Issue 7 (May 2019) - Pourbaba, Masoud; Sadaghian, Hamed; Mirmiran, Amir
In this research, the flexural and shear behavior of five locally developed ultra-high-performance fiber-reinforced concrete beams was experimentally investigated. Four-point loading tests were carried out on concrete specimens which were further compared with five normal-strength concrete beams constructed at the laboratory. The objective of this study is to assess the flexural and shear behavior of ultra-high-performance fiber-reinforced concrete beams and compare them with that of normal-strength beams and available equations in the literature. Results indicate underestimation of shear (up to 2.71 times) and moment capacities (minimum 1.27 times, maximum 3.55 times) by most of the equations in beams with low-reinforcement ratios. Finally, results reveal that the experimental flexural and shear capacities of ultra-high-performance fiber-reinforced concrete specimens are up to 3.5 times greater than their normal-strength counterpart specimens.